Drivers' willingness to drive in old age: a case study on young and mid-aged drivers in China. Issue 4 (November 2016) - Zhang, Weihua; Gu, Jinbiao; Wang, Kun; Du, Yingjie; Feng, Zhongxiang
Abstract Previous studies on driving have found connections among age, gender, perceived driving ability, self-regulatory behavior and driving intentions. However, young and mid-aged drivers' willingness to drive in old age has not been examined in prior studies. The aim of the present study was to gain a better understanding of Chinese drivers' willingness to drive in old age as well as the influence of predictors of this willingness. A sample of 334 participants (aged 20–62 years) completed the perceived driving abilities scale, the driving willingness scale and scales of driving behavior and general information. A multivariate logistic model was used to explore the factors that changed individuals' willingness to drive in old age. The results indicated that drivers' willingness to drive in old age was significantly correlated with age, current driving experience and perceived driving ability in the future. With respect to drivers' perceived driving abilities, visual acuity and executive skills were important predictors of drivers' willingness to drive in old age. In addition, both subjective attitudes and objective attitudes significantly impaired drivers' willingness. Conversely, we found that drivers' willingness to drive increased with restrictive measures. These findings extend our understanding of how attitudes and awareness can influence drivers' willingness to drive in old age. Although drivers' current willingness may subsequently change, the findings are valuable for the study of the driving behavior of older drivers in China.